The relationship between betatrophin levels and HbA1c (Annals of Medical Research, 2021)
Aim: In our study, we first aimed to investigate the effect of betatrophin in uncontroled diabetes patients with HbA1c above 14. Another focus of our study is the effect of betatrophin levels on the biochemical parameters of the patients. Material and Methods: This is an observational study with a prospective case-control design. The study was carried out between July 2018 and November 2018 at the internal medicine clinic of the tertiary university hospital. Our study was conducted with participants divided into 3 groups. Group 3 (uncontrolled T2DM) consisted of 40 participants who met the study criteria and HbA1c above 14% . Group 2 (controlled T2DM) consisted of 40 participants who met the study criteria and HbA1c below %10 and the group 1 (control group) consisted of 40 people who did not have a history of diabetes mellitus.Results: There was no statistical difference in age and sex between the 3 groups included in the study. Betatrophin levels of patients with uncontrolled diabetes were significantly higher than control group and controlled diabetic group.(p0.001). HbA1c value of the participants was found to have a significant effect on betatrophin level, unlike other parameters.(p0.001).Conclusion: We found higher betatrophin levels in the group with uncontrolled diabetes in our study. There was no significant difference in betatrophin levels between the controlled T2DM group and the healthy group. Our data found that betatrophin level showed a significant positive correlation with HbA1c level.
Keywords: Betatrophin; HbA1c; diabetes mellitus